Exploring the Need for Interactive Learning Multimedia to Foster Students’ Mathematical Computational Thinking - Ardon Jamdin; Zaenuri Zaenuri; Scolastika Mariani; Bambang Eko Susilo (CV. Samuel Manurung and Co, 2026)
This study aims to investigate students’ needs for Interactive Learning Multimedia (ILM) in relation to their level of computational thinking in mathematics. Employing a descriptive quantitative approach with a needs analysis survey method, the research involved 30 eighth-grade students at one of the junior high schools in Ambon City. Data was collected using questionnaires assessing both computational thinking levels and ILM needs, based on indicators such as ease of understanding, motivation, visual support, learning interest, and student expectations toward multimedia use. The results indicate that a significant number of students fall into low to moderate levels of computational thinking, while 53% of them demonstrated moderate to high needs for ILM in the learning process. Furthermore, Spearman’s rho analysis revealed a strong and statistically significant correlation (r = 0.863, p < 0.01) between students’ computational thinking skills and their need for multimedia support. These findings highlight the importance of integrating ILM as a pedagogical strategy to enhance students’ logical reasoning, problem-solving skills, and engagement in mathematics learning. The study suggests that well-designed, interactive multimedia can effectively support students’ gradual development in computational thinking.